Fast Dynamic Field-Oriented Control Using Direct Large Voltage Vector and Hysteresis Switch - Al-Kaf, Hasan Ali Gamal; Lee, Kyo Beum (ICPE 2023-ECCE Asia - 11th International Conference on Power Electronics - ECCE Asia: Green World with Power Electronics, 2023)
Field-oriented control (FOC) has been widely used for controlling the current control of permanent magnet synchronous motors (PMSMs) due to its excellent performance in steady-state operation. FOC suffers from slow dynamic response, as a result, its practical use may be limited for applications that require a very fast dynamic response. Accordingly, in this paper, a fast dynamic FOC (FFOC) for PMSM based on a real voltage vector and hysteresis switch is proposed. The hysteresis switch uses FOC in steady-state and the direct real voltage vector in transient-state. Simulation results show that the proposed model has similar steady-state performance as FOC. In addition, FFOC shows faster dynamic performance when FOC and model predictive control (FOC-MPC) are combined using hysteresis switch.
Keywords: Dynamic fields; Fast dynamics; Field-oriented control; Hybrid model; Model-predictive control; Performance; Permanent Magnet Synchronous Motor; Steady-state operation; Voltage hysteresis; Voltage vectors; field-oriented control; hybrid model; model predictive control; PMSM